Diabetes-Related Distress and Depressive Symptoms Are Not Merely Negative over a 3-Year Period in Malaysian Adults with Type 2 Diabetes Mellitus Receiving Regular Primary Diabetes Care - Chew, Boon-How (Front Psychol, 2017)
For people with type 2 diabetes mellitus (T2DM) the daily maintenance of physical and psychological health is challenging. However, the interrelatedness of these two health domains, and of diabetes-related distress (DRD) and depressive symptoms, in the Asian population is still poorly understood. DRD and depressive symptoms have important but distinct influences on diabetes self-care and disease control. Furthermore, the question of whether changes in DRD or depressive symptoms follow a more or less natural course or depend on disease and therapy-related factors is yet to be answered. The aim of this study was to identify the factors influencing changes in DRD or depressive symptoms, at a 3-year follow-up point, in Malaysian adults with T2DM who received regular primary diabetes care. Baseline data included age, sex, ethnicity, marital status, educational level, employment status, health-related quality of life (WHOQOL-BREF), insulin use, diabetes-related complications and HbA1c. DRD was assessed both at baseline and after 3 years using a 17-item Diabetes Distress Scale (DDS-17), while depressive symptoms were assessed using the Patient Health Questionnaire (PHQ-9). Linear mixed models were used to examine the relationship between baseline variables and change scores in DDS-17 and PHQ-9. Almost half (336) of 700 participants completed both measurements. At follow-up, their mean (SD) age and diabetes duration were 60.6 (10.1) years and 9.8 (5.9) years, respectively, and 54.8% were women. More symptoms of depression at baseline was the only significant and independent predictor of improved DRD at 3 years (adjusted β = −0.06, p = 0.002). Similarly, worse DRD at baseline was the only significant and independent predictor of fewer depressive symptoms 3 years later (adjusted β = −0.98, p = 0.005). Thus, more “negative feelings” at baseline could be a manifestation of initial coping behaviors or a facilitator of a better psychological coaching by physicians or nurses that might be beneficial in the long term. We therefore conclude that initial negative feelings should not be seen as a necessarily adverse factor in diabetes care.